Analisis Pelat Lantai Menggunakan Metode Hirzfeld - Mahfuz Hudori; Novia Siti Rohana (LPPM Universitas Abdurrab, 2021)
At this time construction of the royal house is growing very fast at Batam City. The matter proves that are people's construction is successfully for planning the building at Batam City. Floor Slab Analysis with Hirzfeld Method done for knowing the main deflection coefficient and flexible moment of the floor slabs with different dimensions are have different four cases. After analyzed then, obtain results that are the higher dimension of the floor slab then obtain the higher deflection coefficient and flexible moment also.